Pharmacognostical studies of Ricinus communis under the influence of industrial effluent - TYAGI, KAVITA; RASHMI, RAJAT; KHAIR, SHAHIDUL (The Indian Journal of Agricultural Sciences, 2015)
The aim of the present study is to evaluate the pharmacognostical markers of Ricinus communis L., an attempt has been made for a comparative study of plants growing near the vicinity of polluted, Atlas Cycles Industry, with those plants growing in non-polluted areas (ALTT Centre, Ghaziabad,India).It was noted that the industrial effluents not only changed the morphological and anatomical characters of plants, but also affected their chemical constituents. Analysis details contain data regarding colour, odour, BOD, COD, DO, pH, temperature, TS, TSS, TDS, oil and grease, heavy metals etc. which were found to have greater values as compared to standard values. Themorphological, anatomical parameters (xylem vessels, cambium and endodermis are in discontinuous manner, stomatal index, palisade ratio etc.) and physico-chemical parameters (number of spots in observation of TLC, water extractive and alcohol extractive values etc.) have shown a decreasing trends in those plants which were collected near the vicinity of Atlas cycle industry.